Quality Analysis and Critical Control Points (QACCP) for Sustainable Value Chain of Bhutan Organic Black Tea - Wangchuk, Pelden; Boonreang, Supot; Wattanakul, Watcharapong; Chanrattanayothin, Phatthanawan; Lhamo, Jambay; Panyoyai, Naksit (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— Black tea is a health drink rich in polyphenolic compounds with antioxidant properties, making it a beverage that represents the culture of both in Europe and Asia. Black tea is an economically significant product in Bhutan, as it is a community-based product under the One Gewog One Product (OGOP) initiative. Therefore, black tea represents the Bhutanese and reflects the process of selecting tea leaves and processing them using the Orthodox method. This research developed a system called the Quality Analysis of Critical Control Points (QACCPs) to control the quality of tea leaves from the plantation to be processed black tea. The study methodology was divided into three parts: 1) studying the community context, 2) studying the value chain of black tea and 3) applying QACCP based on risk analysis and screening quality to avoid potential hazards in the tea production process. The study found that the black tea produced by the Samcholing Tea Cooperation is made from an organic farming system, with the involvement of women in harvesting, withering, rolling, fermenting, and drying the tea, all of which are critical quality control points. The study also emphasized controlling hazards from physical contaminants such as stones, soil, and wood. An important value of the tea produced from this source is the promotion of women's empowerment through the development of supplementary careers in black tea processing, along with the establishment of a national tea learning center.